A new pseudo three-dimensional hydrodynamic model with Lagrangian vertical mixing and Eulerian horizontal mass exchange. (September 2021) - Zhou, Wencai; Imberger, Jörg; Marti, Clelia Luisa
Abstract: The Multi-Basin DYnamic Reservoir Simulation Model (MB-DYRESM) has been developed to bridge the gap between the computationally cheap, one-dimensional lake models and the computationally expensive, three-dimensional lake models. It was extended from the classic one-dimensional lake model DYRESM by incorporating a horizontal water exchange algorithm to simulate gravitational mass transport between adjacent sub-basins. Numerical experiments with increasing complexity were carried out for capacity demonstration, in which MB-DYRESM successfully reproduced the thermal structure and mass distribution in each sub-basin with accuracy comparable to and computational speed approximately 300 times faster than the three-dimensional model applied in parallel. In situations where turbulence was suppressed by stratification it actually provided better simulation results. The combination of low computational demand, reasonable spatial resolution of mass flux path and constrained numerical diffusion makes MB-DYRESM a more applicable option for simulations where the balance between affordable computational power and proper spatial resolution is concerned. Highlights: MB-DYRESM bridges the gap between one-dimensional and three-dimensional lake models. MB-DYRESM uses a Lagrangian scheme to avoid the accumulative numerical diffusion seen in three-dimensional models. MB-DYRESM simulates horizontal mass transfer with a gravitational water exchange algorithm. MB-DYRESM can be coupled with biogeochemical models to assess impacts of global warming and nutrient enrichment in lakes.